A qualitative investigation on factors that influence knowledge sharing in organizations - Lee, Angela Siew Hoong *; Lim, Tong Ming * (2013)
Factors that influence knowledge sharing among knowledge workers in organizations can seriously affect performance and productivity because poor understanding of these factors can de-motivate knowledge sharing culture and attitude in the organizations The aim of this investigation is to study the factors that influence knowledge sharing in organization and the relationship between those factors. The study looks at six factors: Information Technology, Learning Strategy, Outcome Expectations, Trust, Reward and the role of affect in this research. The role of Affect is introduced into this research base on strong evidence highlighted by many related works that support the significance of affect that can influence knowledge sharing in organizations. This research interviewed 13 individuals from a total of five (5) participating organizations to collect their views on questions designed to solicit important details pertaining to factors discussed above. The outcomes of our findings highlight that the Information Technology Use on KS tools functions need to be more intuitively interesting. As for Learning strategy, participants express that they are happy to share knowledge on the job with some say there is a need to have proper learning strategies in the organizations. On the Reward, interviewees mostly agree that rewards are motivator. On Trust, findings highlight that policy and procedures, validation and source of the information are three key considerations that provide the level of trust on the knowledge obtained and reliability. As for the element of affect, most of the participants highlight that if they are emotionally unpleasant they either provide very little responses on queries forwarded to them, don’t entertain colleagues, or postpone their responses.